PEMELIHARAAN IKAN PATIN (Pangasius sp.) DENGAN TEKNOLOGI BIOFLOK PADA PADAT TEBAR BERBEDA - Ginanjar Adi Sutama; ade dwi sasanti; ferdinand taqwa (Universitas Sriwijaya, 2016)
ABSTRACT Biofloc is a water quality management technology by heterotrophic bacteria development and control, so as to increase the carrying capacity of cultivation media. Good medium carrying capacity can increase the stocking density of fish in aquaculture. The research objective is to determine the stocking density on the rearing catfish (Pangasius sp.) with biofloc technology. Rearing was on May – June 2015 in Aquaculture Laboratory, Department of Aquaculture, Faculty of Agriculture. Research using Completely Randomized Design (CRD) consists of five treatments that stocking density 100 fish.m-3 without biofloc technology (G0), 100 fish.m-3 (G1), 200 fish.m-3 (G2), 300 fish.m-3 (G3), and 400 fish.m-3 (G4) with biofloc technology. The results showed, stocking densities 400 fish.m-3 can still be applied, with the average growth in absolute length of 4.55 cm, growth in absolute weight of 16.82 g, 88.33% survival rate, and 106.5% feed efficiency. Key words : Catfish, Biofloc, Stocking density